Arsenate resistance in the unicellular marine diazotroph Crocosphaera watsonii - Dyhrman, Sonya; Haley, Sheean (Frontiers in Microbiology, 2011)
The toxic arsenate ion can behave as a phosphate analog, and this can result in arsenate toxicity especially in areas with elevated arsenate to phosphate ratios like the surface waters of the ocean gyres. In these systems, cellular arsenate resistance strategies would allow phytoplankton to ameliorate the effects of arsenate transport into the cell. Despite the potential coupling between arsenate and phosphate cycling in oligotrophic marine waters, relatively little is known about arsenate resistance in the nitrogen-fixing marine cyanobacteria that are key components of the microbial community in low nutrient systems. The unicellular diazotroph, Crocosphaera watsonii WH8501, was able to grow at reduced rates with arsenate additions up to 30 nM, and estimated arsenate to phosphate ratios of 6:1. The genome of strain WH8501 contains homologs for arsA, arsH, arsB and arsC, allowing for the reduction of arsenate to arsenite and the pumping of arsenite out of the cell. The short-term addition of arsenate to the growth medium had no effect on nitrogen fixation. However, arsenate addition did result in the up-regulation of the arsB gene with increasing arsenate concentrations, indicating the induction of the arsenate detoxification response. The arsB gene was also up-regulated by phosphorus stress in concert with a gene encoding the high-affinity phosphate binding protein pstS. Both genes were down-regulated when phosphate was re-fed to phosphorus-stressed cells. A field survey of surface water from the low phosphate western North Atlantic detected expression of C. watsonii arsB, suggestive of the potential importance of arsenate resistance strategies in this and perhaps other systems.